2013
DOI: 10.3346/jkms.2013.28.2.195
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Varicella-Zoster Virus in Korea

Abstract: This study was designed to assess the immune status of the Korean population against varicella-zoster virus (VZV) through a seroepidemiologic study. Residual blood samples were collected from diagnostic laboratories throughout Korea. Samples were collected in October 2009 to March 2010 from persons 0-79 yr of age and were tested by ELISA (Enzygnost®; Dade Behring, Schwalbach, Germany). Total seroprevalence in subjects 1-79 yr of age was 89.6%. Seroprevalence increased as age increased from 67.3% in subjects 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 14 publications
2
21
1
Order By: Relevance
“…A cross-sectional study in four Korean hospitals tested the seroprevalence of 887 patients in which overall 87.6% had anti-VZV IgG antibody [25]. [26]. The decreasing trend of antibody level may explain the continuing increase of varicella in all given cohorts despite the introduction of the vaccine into the national immunisation programme.…”
Section: Epidemiology and Infectionmentioning
confidence: 99%
“…A cross-sectional study in four Korean hospitals tested the seroprevalence of 887 patients in which overall 87.6% had anti-VZV IgG antibody [25]. [26]. The decreasing trend of antibody level may explain the continuing increase of varicella in all given cohorts despite the introduction of the vaccine into the national immunisation programme.…”
Section: Epidemiology and Infectionmentioning
confidence: 99%
“…The seroprevalences determined by ELISA showed a similar trend by age group. A previous study, using the same commercial ELISA kit used in the present study, was performed in 2009 in Korea; that study reported a VZV seroprevalence of ~94% in teenage subjects and 98% in subjects aged ⩾20 years [ 22 ]. In the present study, the seroprevalences determined by ELISA were lower than they were in a previous report, 83·3% in teenage subjects and 93·0% in subjects in their twenties and thirties.…”
Section: Discussionmentioning
confidence: 99%
“…For early detection of such epidemiological and seroepidemiological changes, and in order to establish appropriate strategies for controlling breakthrough VZV infections, repeated surveillance of immune status against VZV in the community is necessary. However, only studies including limited numbers of subjects have been performed in Korea [ 20 22 ]. In addition, only one seroepidemiological study for VZV using the fluorescent antibody to membrane antigen (FAMA) test has been performed; this study was limited to adults aged >40 years [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Croatia, the prevalence of VZV-antibody among women of child-bearing age reported equal 84.3% (18). In Italy (19), Tunisia (20) and Korea (21), it has been reported 80.9%, 80.9% and 89.6%, respectively. In 2007, 96.1% of Spanish women during their fertility period were immune to VZV (22).…”
Section: Discussionmentioning
confidence: 99%